Health literacy, mental disorders and fear of progression and their association with a need for psycho-oncological care over the course of a breast cancer treatment. Issue 7 (9th August 2021) - Nakata, Hannah; Halbach, Sarah; Geiser, Franziska; Stock, Stephanie; Kowalski, Christoph; Enders, Anna; Pfaff, Holger; Ernstmann, Nicole
ABSTRACT: This studyinvestigates the need for psycho-oncological care over the course of a breast cancer treatment and possible associated factors to develop such a need. The PIAT-Study was a longitudinal postal survey study conducted in Germany (2013 to 2014) with breast cancer patients (BCPs). Patients received a questionnaire at three-time points (T1: few days after surgery, T2: after 10 weeks; T3: after 40 weeks). This study considers information about patients' needs for psycho-oncological care, their breast cancer disease, social support, anxiety, health literacy (HL) and sociodemographic information. Data were analysed with descriptive statistics and logistic regression modelling to estimate the association between a need for psycho-oncological treatment and patient characteristics. N = 927 breast cancer patients reported their psycho-oncological need. 35.2% of patients report at least at one measuring point to be in need for psycho-oncological care. In a multiple logistic regression, noticeable determinants for developing such a need are an inadequateHL(OR = 1.97), fear of progression (FoP) (OR = 2.08) and psychological comorbidities (OR = 8.15) as well as certain age groups. BCPs with a low HL, suffering from a dysfunctional level of FoP or mental disorders are more likely to develop a need for psycho-oncological care.